2015
DOI: 10.1103/physrevb.91.041201
|View full text |Cite
|
Sign up to set email alerts
|

From two-dimensional electron gas to localized charge: Dynamics of polaron formation in organic semiconductors

Abstract: Electronic transport in organic semiconductors is mediated by localized polarons. However, the dynamics on how delocalized electrons collapse into polarons through electron-nuclear interaction is not well-known. In this work, we use time and angle resolved photoemission spectroscopy (TR-ARPES) to study polaron formation in titanyl phthalocyanine deposited on Au(111) surfaces. Electrons are optically excited from the metal to the organic layer via the image potential state, which evolves from a dispersive to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…2d. The fit gives an electron-phonon scattering rate of 20-30 ps −1 (30-60 fs) and an initial small polaron bimolecular formation rate of 11 ± 0.5 ps −1 (90 ± 5 fs), similar to previous reports for polaron formation [22][23][24] . The competition between electron-phonon scattering to create phonons, then subsequent removal of electrons and phonons in the generation of polarons, leads to the fast rise in small polaron population followed by a slowing down of polaron formation at ∼3 ps in Fig.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…2d. The fit gives an electron-phonon scattering rate of 20-30 ps −1 (30-60 fs) and an initial small polaron bimolecular formation rate of 11 ± 0.5 ps −1 (90 ± 5 fs), similar to previous reports for polaron formation [22][23][24] . The competition between electron-phonon scattering to create phonons, then subsequent removal of electrons and phonons in the generation of polarons, leads to the fast rise in small polaron population followed by a slowing down of polaron formation at ∼3 ps in Fig.…”
supporting
confidence: 87%
“…For transport to occur, phonon motion must bring two Fe centres in proximity, giving the charge carrier a finite probability to hop between atoms. Similar to a mid-gap or surface trap state, the small polaron acts to localize the carrier to a specific site until sufficient thermal energy is present for conduction [22][23][24][25] . Given that polaron formation is accelerated at defect sites, small polaron formation also acts to trap mobile carriers at recombination centres 21 .…”
mentioning
confidence: 99%
“…Previous ultrafast surface science investigations have shown that the dynamics of an electronic state in a molecular film can differ based on the molecular properties of the film, the electronic state localization, influence of the metal substrate, and molecular film thickness. 8,10,[27][28][29][30][31][32][33][34][35] The contrasting dynamics of electron localization in nonpolar n-heptane versus polar water and ammonia highlight the influence of the molecular properties of the film. In ultra-thin non-polar n-heptane layers on a Ag(111) surface, electron injection leads to the formation of small polarons that are self-trapped via the in-phase methylene rocking of n-heptane on an approximately 360 fs timescale.…”
Section: Introductionmentioning
confidence: 99%
“…The IPS is distinct from other peaks in the time-resolved spectrum, since it has a negative lifetime (it is pumped by the UV pulse and probed by the visible pulse). The IPS has been studied previously [44,45] and is outside the scope of this work. In this work, we will focus on the S 1 state.…”
Section: A Energy-level Alignment At the Interfacementioning
confidence: 99%